Systemic photodynamic therapy with photosensitizer photolon in the treatment of cancer patients with regional and distant metastases - M. A. Kaplan; A. M. Shubina; I. A. Zamulaeva; E. I. Selivanova; E. G. Kuz’mina; N. P. Tkachenko; I. G. Zakurdyaeva; V. N. Kapinus; E. V. Goranskaya (Biomedical Photonics, 2014)
The results of photodynamic therapy (PDT) in 76 patients with tumors of different sites and with regional or distant metastases are represented. Sixty three patients were under combined or multimodal therapy, 13 patients had systemic PDT as monotherapy. The technique of PDT was as follows: the solution of photosensitizer photolon was administered intravenously at dose of 0.8–1.4 mg/ kg body weight. Laser blood irradiation was performed simultaneously (wavelength of 662 nm, output power of 20 mW, irradiation time of 50 min). Stabilization of the disease defined as the absence of new tumor foci was observed in 55% of treated patients: among them in 47% of patients with disseminated melanoma during 6–10 months after treatment, in 65% patients with breast cancer – for 3–6 years after treatment, and also in 100% of patients with cancer of other sites (colorectal, pancreatic, cervical, ovarian, lung and stomach cancer, retroperitoneal neuroblastoma) – for 10–12 months after treatment. According to ultrasound data the shrinkage of most of metastases up to its complete disappearance was observed. The authors consider that effects of systemic PDT are due to decrease of circulating tumor cells in blood and also due to beneficial impact of this modal of treatment on immune status of cancer patient. Intravenous PDT was shown to improve treatment results and quality of life in patients with metastases of malignant tumors. The approved technique is of considerable interest and requires further investigation of its efficiency including its combination with methods of combined and multimodal treatment.